Therapeutic Benefits of Saffron in Brain Diseases: New Lights on Possible Pharmacological Mechanisms - Sharma, Bhupesh; Kumar, Hariom; Kaushik, Prachi; Mirza, Roohi; Awasthi, Rajendra; Kulkarni, T. Giriraj (ELSEVIER, 2020)
Saffron is dried stigmas of Crocus sativus flowers, an extensively used spice and food additive because of its color and taste. Biologically, Saffron belongs to the carotenoid family with major active components such as crocin, safranal, and crocetin. Saffron has widely been used for traditional and herbal medicine. Clinically, Saffron has shown both safety and efficacy in mild to moderate Alzheimer's disease. Saffron has the neuroprotective activity because of its chemical active moieties. Saffron's efficacy has been examined in some brain diseases such as Alzheimer's disease, Parkinson's disease, cerebral ischemia, and depression because of its chemically active moieties. In this chapter, we have explored the pharmacological insight of saffron for its benefits in brain-related diseases. It has been proposed that Saffron and its actives have the modulatory action on acetylcholinesterase activity, dopaminergic signaling, amyloid-β (Aβ), free radical scavenging activity, microglial activation, mitochondrial function, notch signaling pathway, Keap1/Nrf2 signaling pathway, nuclear dactor. -κ. B activation, mitogen-activated protein kinases signaling, and Aβ. On other hand, Saffron has shown to counteract altered behavioral parameters such as learning and memory, motor function, and seizures in experimental brain diseases. It may be proposed possibly that saffron can serve as therapeutic herbal medicine for various brain-related conditions in humans. The exact mechanisms for the neuroprotection are not explicitly known. This chapter tries to shed a light on possible mechanisms to provide one of the research directions for molecular biologists and pharmacologists.
Keywords: Central nervous system; Crocin; Crocus sativus; Pharmacology; Saffron; Safranal and crocetin